The magus: A new identity through art - BAKIR, CAHİT (My University, 2017)
The purpose of this paper is to explore the function of art in John Fowles’s The Magus in relation with existential terminology. It focuses on Fowles’s inseparability of life and art theme and tries to disclose how Nicholas, the protagonist of the novel, is directed towards a process of education through art in order to redefine his notion of self. The study aims to manifest that Nicholas can achieve a higher sense of reality and create his own existence in his search for selfhood or self-realization instead of adhering to his former artificial identity and inauthentic life shaped by the external circumstances. In the process of his psychological journey towards self-identity, the references to various art forms will be analyzed in depth to disclose the fact that it is art that will prompt Nicholas to attain a new sense of freedom in line with Fowles’s notion that life imitates art. In that regard, it will be emphasized that the autonomy of the text and the writer is undermined in the novel as postmodernism stresses heterogeniety and multiplicity of meanings. As postmoderntheory suggests, the production of a text should be regarded as an intertext which means that a text is a compilation of other texts because it is comprised of references to other texts. Fowles’s The Magus, as a postmodern text, combines a variety of allusions to other literary, scientific and sociological texts and includes a great deal of references to other art forms such as paintings, music and sculpture. By referring to such art forms, Fowles aims to initiate an inner journey in Nicholas towards the core of his self. In this study, the relation of existentialism with the text will be stressed as well. That is, it will be revealed that in The Magus, John Fowles tries to free his male protagonist Nicholas from external circumstances to redefine both his notion of self and the world according to 20th century existential terminology.
Keywords: Sosyal ve Beşeri Bilimler; Dil ve Edebiyat; Batı Dilleri ve Edebiyatları; İngiliz Dili ve Edebiyatı; Social Sciences and Humanities; Philology; Western Languages and Literatures; English Language and Literature; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; EDEBİYAT, ALMAN, HOLLANDA, İSKANDİNAV; EDEBİYAT, İNGİLİZ ADALARI; EDEBİYAT; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; LITERATURE, GERMAN, DUTCH, SCANDINAVIAN; LITERATURE, BRITISH ISLES; LITERATURE; Edebiyat ve Edebiyat Teorisi; Sosyal Bilimler ve Beşeri Bilimler; Literature and Literary Theory; Social Sciences & Humanities